1995
DOI: 10.1103/physrevlett.75.217
|View full text |Cite
|
Sign up to set email alerts
|

Do Hollow Atoms Exist in Front of an Insulating LiF(100) Surface?

Abstract: First measurements of ALL Auger spectra arising from collisions of N + ions on an insulating LiF(100) surface are presented. The beam energy is varied from 0.08 up to 16 keV. The incident angle is chosen such that the perpendicular velocity component is constant over the indicated energy range. Spectral features arising from above surface KLL emission, observed during interaction of N + with a conducting Si(100) surface, are absent for LiF, implying pronounced differences in the dynamics governing the above-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…It is interesting to note that the target with the greatest electron yield is not the gold, but the HOPG. It is also interesting to note that an insulating target CaF 2 has a larger electron emission yield than the gold target in agreement with the recent results for another insulator LiF (Limburg et al 1997). It is possible that in the case of an insulator the target charges up as electrons are removed from the surface.…”
Section: Image Charge Acceleration and Distance Of First Electron Capsupporting
confidence: 83%
“…It is interesting to note that the target with the greatest electron yield is not the gold, but the HOPG. It is also interesting to note that an insulating target CaF 2 has a larger electron emission yield than the gold target in agreement with the recent results for another insulator LiF (Limburg et al 1997). It is possible that in the case of an insulator the target charges up as electrons are removed from the surface.…”
Section: Image Charge Acceleration and Distance Of First Electron Capsupporting
confidence: 83%
“…We reproduce this result, measuring slightly higher yields from Si02 than from Au for incident protons and 03+ ions. It has been suggested that hollow atom formation is strongly inhibited for impact of highly charged ions like~and Ne* [7] on insulators like LiF. Winter et al [4] found that less efficient above surface electron emission was more than compensated by more efficient below sutiace emission from LiF, resulting in higher electron yields from LiF than from Au targets for impact of slow HCI with q<lO+.…”
Section: Experimental Arrangementmentioning
confidence: 99%
“…Whh most electrons populating high n Rydberg states, a highly excited, but neutral "hollow atom" finally hits the surface. It has been suggested that hollow atom formation in front of insulator surfaces is relatively inhibited in comparison to impact on metals [7]. At impact, electrons in Rydberg states with radii in excess of a characteristic surface screening length are -peeled off, and a fraction of eleotrons escapes into the vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…1; for more details, see Skobelev et al, 2012). Transitions of this kind were also observed in experiments on the interaction of the ion beams (Briand et al, 1996;Bailey et al, 1990;Limburg et al, 1995;Ninomiya et al, 1997;Winter et al, 1999;Schenkel et al, 1999;McMahon et al, 2011;Rzadkiewicz et al, 2010), synchrotron radiation (Diamant et al, 2000b;2000a;, or X-ray free electron laser beams (Vinko et al, 2012) with a solid target. The first observation of the similar emission pattern for multi-charged ions was done at the Naval Research Laboratory's NIKE KrF laser facility using ns laser pulses (Aglitsky et al, 1996).…”
Section: Introductionmentioning
confidence: 79%